Pharmacogenetics, epigenetics and pharmacoepigenetics - Sorin Buzinschi (Amaltea Medical Publishing House, 2020)
Modern genetic studies have allowed the development of new disciplines that have high hopes for the treatment of severe conditions such as cancer and HIV/AIDS. The application of the notions of pharmacogenetics and pharmacoepigenetics, largely still under the sign of research, opens new horizons for medical and pharmaceutical practice.